The Effects of Hybrid Learning Modality to the Budget of the Families in Novaliches, Quezon City Year 2022-2023: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Due to the pandemic caused by COVID-19, many families in Novaliches Quezon City havelost their livelihoods, jobs, and businesses. DepEd decided to have a learning modalitycalled the Hybrid learning modality. Because of the hybrid learning modality, the researcherswant to determine if the families in Novaliches Quezon City have a problem in terms of theirexpenses and needs, if each family is financially ready in Novaliches in new learningmodality, and this study also aimed to determine the effects of hybrid learning modality to thebudget of the families in Novaliches Quezon City.It was figured out that hybrid learning affected the respondents' budgets in NovalichesQuezon City. Furthermore, Results showed that the budget of the families in NovalichesQuezon City does not fit their different expenses and needs.This discussion is based on our recommendations that researchers can recommend toothers who will do a research study about the title effect of hybrid learning modality on thebudget of the families in Novaliches Quezon City because, as you can see, this discussionhas a lot of knowledge that can be used as a step by researchers.
Keywords: Business Administration